Courage Has No Color, The True Story of the Triple Nickles: Americas First Black Paratroopers - Stone, Tanya Lee. (New York, NY : Scholastic Inc., 2013)
Examines the role of African-Americans in the military through the history of the Triple Nickles, Americas first black paratroopers, who fought against attacks perpetrated on the American West by the Japanese during World War II.
"This edition is available for distribution only through the school market."--P. [4] of cover.
1090
Keywords: United States -- Army; Parachute Infantry Battalion, 555th; History; Juvenile literature; United States -- Army -- African American troops; History -- 20th century; Juvenile literature; United States -- Army -- Parachute troops; History -- 20th century; Juvenile literature; World War, 1939-1945 -- Regimental histories -- United States; Juvenile literature; World War, 1939-1945 -- Participation, African American; Juvenile literature; World War, 1939-1945 -- Campaigns -- Western Front; Juvenile literature; African American soldiers; History -- 20th century; Juvenile literature; African Americans -- Social conditions -- To 1964; Juvenile literature; Race discrimination -- United States; Juvenile literature; History; Juvenile works